Biofilms affecting progression of mild steel corrosion by Gram positive Bacillus sp. (1st April 2015) - Lin, Johnson; Madida, Bafana B.
<x xml:space="preserve">Abstract</x> The biodeterioration of metals have detrimental effects on the environment with economic implications. The deterioration of metals is of great concern to industry. In this study, mild steel coupons which were immersed in a medium containing Gram‐positive Bacillus spp. and different nutrient sources were compared with the control in sterile deionized water. The weight loss of the coupons in the presence of Bacillus spp. alone was lower than the control and was further reduced when additional carbon sources, especially fructose, were added. The level of metal corrosion was significantly increased in the presence of nitrate with or without bacteria. There was a significant strong correlation between the weight loss and biofilm level (r = 0.64; p < 0.05). The addition of nitrate and Bacillus spp. produced more biofilms on the coupons and resulted in greater weight loss compared to that with Bacillus spp. only under the same conditions. However, Bacillus spp. enriched with carbon sources formed less biofilms and results in lower weight loss compared to that with Bacillus spp. only. The production of biofilm by Bacillus spp. influences the level of metal corrosion under different environmental conditions, thereby, supporting the development of a preventive strategy against corrosion.